Impact of Peritoneal Dialysis Treatment on Arterial Stiffness and Vascular Changes in Diabetic Type 2 and Nondiabetic Patients with End-Stage Renal Disease - Damir Rebić; Senija Rašić; Velma Rebić (International Journal of Nephrology)
Diabetes mellitus (DM) is the leading cause of the end-stage renal disease (ESRD). Vascular diseases are the most common cause of morbidity and mortality in the chronic kidney disease. The aim of this study was to analyze the impact of peritoneal dialysis (PD) treatment on morphologic and hemodynamic vascular parameters of carotid arteries in diabetic type 2 and nondiabetic patients with ESRD during the period of one year after the start of PD treatment using ultrasonography of carotid arteries and their relation on uremia and PD inherent factors. Mean intima-media thickness, plaque score, peak systolic velocity, end-diastolic velocity, and carotid diameter significantly decreased 12 months after PD treatment start in both groups. Significant reduction in median serum endothelin-1 concentration after 12 months on PD treatment was observed in the group of patients with DM (7.6–5.9 pg/mL) and also in group of patients without DM (3.6–3.3 pg/mL). Also median nitric oxide concentration significantly increased after 12 months on PD compared to baseline levels both in patients with DM (25.0–34.3 μmol/L) as was observed in patients without DM (49.6–56.5 μmol/L). PD treatment, with the regulation of these vasoactive molecules and other vascular risk factors, significantly contributes to vascular remodeling, especially in DM patients.